Development of Arabic Dialogue Teaching Materials Based on A Contextual Approach for Developing Speaking Skills | تطوير مواد الحوار على أساس مدخلا لسياقي لترقية مهارة الكلام - Fuadi, Abdul Hafizh Nur; Ulum, Miftahul; Sunnah, Muqimah Liwais (NAJAH BESTARI, 2023)
This research is motivated by the importance of learning Hiwar in improving Arabic Speaking Skills. Arabic Speaking Skills can be improved with Mumarosah or Habituation. To support habituation, teaching materials must be supported that are appropriate to daily habits. Therefore, researchers created Hiwar teaching materials with a contextual approach. This research uses an R&D method, with the Brogand Gall development model. In the Brogand Gall development model there are 10 development steps. The product T test results obtained t-count 8.882 > t-table 1.703. So that the product created has effectiveness and efficiency in improving peak Arabic language skills with a confidence level of 11% through post-test results which are higher than the pretest. Based on the research results, Hiwar teaching materials with a contextual approach are intended for 3rd semester students as an appropriate reference and can improve students' Arabic speaking skills. This research only reached the second chapter of the material due to time constraints. Karina hopes that future researchers will be able to complete the development material up to the sixth chapter as originally planned.